(untitled) (Research, Society and Development, 2018)
The objective of this work was to analyse the perception of business people on the evolution of the Accountant profile, considering the significant increase of it´s importance with the advent of international accounting standards. Therefore the following question was elaborated: what the perception of business people on the evolution of the Accountant profile? As for the methodological procedures, this study is classified as quantitative according to the approach, descriptive regarding the objectives and as a survey of the procedures. The data collection was done through the questionary containing eighteen closed questions and validated by three teachers in the area. A universe of 62 entrepreneurs, clients of an accounting office in the city of São José, state of Santa Catarina, was searched by e-mail, created through the tool google forms, and a sample of 53 (fifty three) respondents, representing 85% of the population surveyed. The main results pointed that the business people perceive this evolution in the accounting professional profile, consider he essential for the business and would keep the accounting writing if they were not obliged. However, international accounting standards were not considered influential in the evolution of the Accountant profile and there are limitations on the use of their competences by business people.